Evaluación de bacterias solubilizadoras de minerales en el desarrollo morfológico de cacao CCN-51 y su capacidad protectora contra Phytophthora palmivora - Macías Holguín, Cristhian John (2021)
Black pod rot is the most important factor limiting cocoa (Theobroma cacao) production, with annual losses exceeding 30%. The use of biological control agents using microorganisms is considered one of the safest and most affordable strategies. The objective of this study was to evaluate mineral solubilizing bacteria in the morphological development of cocoa CCN-51 and its protective capacity against Phytophtora palmivora. In the present work, 238 strains were isolated from different parts of the plant with potential to solubilize nutrients, biostimulants and bioprotective capacity against P. palmivora. Nine isolates obtained from a biochemical screening with catalase production, protease, siderophore production, gram staining and morphological characters were selected. The 9 strains were subjected to N-P-K solubilization assays, emphasizing that strain BF-567 reached the highest solubilization percentage with superior averages of 81%, 90% and 100%, standing out from the rest of the treatments under study. In addition, the biostimulant effect of the bacterial sediment of strain FZ 9-7 washed with PBS (Phosphate Buffered Saline) was observed, presenting higher results in germination rate of 100%, length 5.67 cm, weight 3.57 g and root volume 92.43 cm3. Also, these isolates were analyzed to determine the antagonistic activity by bacteria-pathogen and supernatant-pathogen confrontations, in dual culture and direct supernatant sweep assays. Strains FZ 9-7 and BF-567 were able to inhibit mycelial growth progress in vitro in the range of 86% and 85% through the production of antifungal compounds. These results confirm the importance of rhizobacteria and suggest that these bacteria could be used for biological control of soil oomycetes through their volatile emissions. Key words: NPK solubilization, Phytophtora palmivora, biostimulant, protease, supernatants, PBS buffer.